Saudi consumers' perceptions of foreign products / M. Sadiq Sohail (Faculty of Business and Management ; UiTM Press, 2005)
The objective of this paper is to examine the Saudi consumers' perception of products made overseas and the country of origin effect of products. While a limited number of studies have been conducted in this area in the past, this study assumes importance due to the changing attitudes and perception of some Saudi consumers towards certain countries in the new millennium. The study reports on the findings of a survey conducted in which 922 responses were obtained. In general, Saudi consumers evaluate products from Japan and the European Union more favorably as compared to products from the United States of America, China and India. The study discusses the results of other empirical findings.